Effect of age related changes in chamber size, wall thickness, and heart rate on left ventricular function in normal children. Issue 4 (October 1982) - St John Sutton, M G; Marier, D L; Oldershaw, P J; Sacchetti, R; Gibson, D G
Abstract : We assessed the effects of age related changes in chamber size, wall thickness, and heart rate of left ventricular function in 78 normal children, aged 1 1/2 to 12 1/2 years, using computer analysis of their left ventricular echocardiograms. Left ventricular cavity size and wall thickness increased linearly with age. Left ventricular fractional shortening, percentage of wall thickening, and the ratio of end-diastolic wall thickness to cavity radius (H/R ratio) did not change with age. Peak Vcf correlated with heart rate and the decrease in heart rate with age resulted in the progressive fall in peak Vcf, while peak rate of left ventricular was thickening remained constant. The peak rate of increase in left ventricular cavity dimension in early diastole varied inversely with heart rate, but independently of cavity size, increasing throughout childhood. The peak rate of wall thinning also increased with age, correlating with wall thickness and not heart rate. Thus, age related increases in left ventricular cavity dimension and wall thickness during the rapid growth period of childhood occurred in such a way that left ventricular architecture (H/R ratio) remained unchanged. This may account for the constancy of regional and cavity systolic function. The greater dependence of diastolic cavity function on heart rate may be explained by the disproportionately greater effect of cardiac cycle length on the duration of diastole and systole.